The Rise of China and Its Impact on Asia: South Korea's Economic Relations with China - Chun, Hong Tack (Korea Development Institute, 1995)
The purpose of this paper is to analyze economic relations between South Korea and China to determine which view of China is more appropriate: China as a competitor or as a partner of economic cooperation for South Korea. We would also like to provide prospects based on economic analysis for future relations between the two countries. Political aspects of relations between South Korea and China will be briefly examined as well to complement economic analysis. (※서문에서 발췌한 내용임)